Performance evaluation of mobile processes via abstract machines. - Nottegar, C.
We use a structural operational semantics which drives us in inferring quantitative measures on system evolution. The transitions of the system are labeled and we assign rates to them by only looking at these labels. The rates reflect the possibly distributed architecture on which applications run. We then map transition systems to Markov chains, and performance evaluation is carried out using standard tools. As a working example, we compare the performance of a conventional uniprocessor with a prefetch pipeline machine. We also consider two case studies from the literature involving mobile computation to show that our framework is feasible
Keywords: Markov chains; Abstract machines; Calculi for mobility; Distributed architecture; Formal methodology; Mobile computation; Mobile processes; Performance evaluation; Prefetch pipeline machine; Quantitative measures; Stochastic models; Structural operational semantics; System evolution; Uniprocessor